Qualitative and Quantitative Micro-CT Analysis of Natal and Deciduous Teeth: A Pilot Comparative Study. - Ravi, Srivarsan; Pooja, Pooja (Journal of Neonatal Surgery, 2024)
Background: Natal teeth are uncommon developmental anomalies present at birth or erupting within the first month of life. Due to their premature eruption and altered developmental processes, natal teeth often exhibit structural and mineralization differences compared to normal deciduous teeth. Micro-computed tomography (micro-CT) offers a non-destructive, high-resolution imaging modality for evaluating dental hard tissues quantitatively and qualitatively. Aim: To compare the morphological characteristics, mineralization patterns, and microstructural properties of natal and deciduous teeth using qualitative and quantitative micro-CT analysis. Materials and Methods: One extracted natal tooth and one extracted deciduous tooth were analyzed using high-resolution micro-computed tomography. Scanning was performed at 90 kV and 100 µA with an isotropic voxel size of 9.9994 µm using a 0.5-mm aluminum filter. Qualitative assessment included evaluation of enamel morphology, dentin architecture, enamel-dentin junction (EDJ), and pulp morphology. Quantitative analysis was performed using CTAn software to determine total volume of interest (TV), object volume (Obj.V), percentage object volume (Obj.V/TV), object surface area (Obj.S), object surface-to-volume ratio (Obj.S/Obj.V), and object surface density (Obj.S/TV). Results: The natal tooth demonstrated reduced mineralized tissue volume, decreased surface density, and increased surface-to-volume ratio compared to the deciduous tooth. The deciduous dentin exhibited the highest object volume (119.50 µm³) and surface density (0.1597), indicating greater mineralization and structural maturity. Qualitative analysis revealed irregular enamel thickness and reduced dentin deposition in the natal tooth. Conclusion: Micro-CT analysis demonstrated significant structural and mineralization differences between natal and deciduous teeth. Natal teeth exhibited immature mineralized tissues with reduced density and altered morphology, whereas deciduous teeth showed greater mineralization and structural organization